2022
DOI: 10.1097/mnh.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of leptin-induced endothelial dysfunction

Abstract: Purpose of reviewEndothelial dysfunction is a major risk factor for many cardiovascular diseases, notably hypertension. Obesity increases the risk of endothelial dysfunction in association with increasing production of the adipokine leptin. Preclinical studies have begun to unravel the mechanisms whereby leptin leads to the development of endothelial dysfunction, which are sex-specific. This review will summarize recent findings of mechanisms of leptin-induced endothelial impairment in both male and females an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Together, these data suggest that Lepr is largely or wholely absent from mouse islet endocrine cells. It has been reported previously that LEPR is expressed in mouse T cells (31,32), endothelial cells (33), and smooth muscle cells (33). Our scRNAseq also demonstrates Lepr expression within islet endothelial cells.…”
Section: Discussionsupporting
confidence: 81%
“…Together, these data suggest that Lepr is largely or wholely absent from mouse islet endocrine cells. It has been reported previously that LEPR is expressed in mouse T cells (31,32), endothelial cells (33), and smooth muscle cells (33). Our scRNAseq also demonstrates Lepr expression within islet endothelial cells.…”
Section: Discussionsupporting
confidence: 81%
“…One review article suggests that intermittent hypoxia, a consequence of sleep-disordered breathing, may impact leptin levels in pregnant women, rather than preeclampsia's pathogenesis ( 22 ). Another study showed that LEP -induced endothelial dysfunction, a possible cause of preeclampsia, might happen even if there are no other health problems related to obesity ( 23 ). The significance of finding elevated LEP mRNA in STB-EVs in the context of PE extends beyond a mere correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Lepr is expressed in mouse T cells ( 62 , 63 ), endothelial cells ( 64 ), and smooth muscle cells ( 64 ). Here, we show the presence of Lepr in mouse islet endothelial cells using publicly available RNAseq data.…”
Section: Discussionmentioning
confidence: 99%